2010
DOI: 10.1007/s13181-010-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

Propafenone Poisoning—A Case Report with Plasma Propafenone Concentrations

Abstract: Propafenone is an anti-arrhythmic drug used in the management of supraventricular and ventricular arrhythmias. It is metabolised through cytochrome P450 2D6 pathways; the major metabolites possess antiarrhythmic activity. The cytochrome P450 CYP2D6 is coded by more than 70 alleles resulting in great genetic polymorphism of CYP2D6 isoenzymes, and up to 7% of Caucasian population are poor metabolisers. This case report describes a patient with severe overdose of propafenone who presented with coma, seizures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…CYP2D6 encodes a subunit of the cytochrome P450 superfamily of enzymes. The gene is specifically expressed in the right ventricle and its genetic polymorphism is known to be associated with cardiotoxicity, including a patient's poor anti-arrhythmic activity, severe cardiovascular, or dilated cardiomyopathy [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…CYP2D6 encodes a subunit of the cytochrome P450 superfamily of enzymes. The gene is specifically expressed in the right ventricle and its genetic polymorphism is known to be associated with cardiotoxicity, including a patient's poor anti-arrhythmic activity, severe cardiovascular, or dilated cardiomyopathy [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to suspect that HCO 3 would benefit patients with propafenone toxicity, but the literature in this setting is limited. Ovaska et al [11] reported a patient that was was managed with intravenous glucagon, sodium bicarbonate, hypertonic saline and this treatment was associated with a good outcome. Recently D'Orazio [12] reported that sodium bicarbonate bolus and infusion shortened the QRS length to 90 ms. To avoid persistent hypotension and ECG abnormalities, 1 mEq/kg sodium bicarbonate administration in every 4-6 hours is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…3). Propafenone is a class 1C (sodium channel blockers) antiarrhythmic drug used for the treatment of ventricular arrhythmias [42]. Propafenone undergoes extensive metabolism via the CYP2D6 and CYP3A4.…”
Section: Toxicological Interactions -Cases Reportsmentioning
confidence: 99%
“…Intoxication with propafenone is rare, a limited number of cases of lethal self-poisoning being reported in the literature [43]. Overdose may induce arrhythmia and conduction disturbance, complex, tachycardia, right bundle branch blocks, congestive heart failure and hypotension, seizures [42]. Interactions of propafenone with diazepam are not documented.…”
Section: Toxicological Interactions -Cases Reportsmentioning
confidence: 99%